Prion Protein Gene (PRNP) Sequences Suggest Differing Vulnerability to Chronic Wasting Disease for Florida Key Deer (Odocoileus virginianus clavium) and Columbian White-Tailed Deer (O. v. leucurus). (18th September 2020) - Perrin-Stowe, Tolulope I N; Ishida, Yasuko; Terrill, Emily E; Hamlin, Brian C; Penfold, Linda; Cusack, Lara M; Novakofski, Jan; Mateus-Pinilla, Nohra E; Roca, Alfred L
Abstract: Chronic wasting disease (CWD) is a fatal, highly transmissible spongiform encephalopathy caused by an infectious prion protein. CWD is spreading across North American cervids. Studies of the prion protein gene ( PRNP ) in white-tailed deer (WTD; Odocoileus virginianus ) have identified non-synonymous substitutions associated with reduced CWD frequency. Because CWD is spreading rapidly geographically, it may impact cervids of conservation concern. Here, we examined the genetic vulnerability to CWD of 2 subspecies of WTD: the endangered Florida Key deer ( O. v. clavium ) and the threatened Columbian WTD ( O. v. leucurus ). In Key deer ( n = 48), we identified 3 haplotypes formed by 5 polymorphisms, of which 2 were non-synonymous. The polymorphism c.574G>A, unique to Key deer (29 of 96 chromosomes), encodes a non-synonymous substitution from valine to isoleucine at codon 192. In 91 of 96 chromosomes, Key deer carried c.286G>A (G96S), previously associated with substantially reduced susceptibility to CWD. Key deer may be less genetically susceptible to CWD than many mainland WTD populations. In Columbian WTD ( n = 13), 2 haplotypes separated by one synonymous substitution (c.438C>T) were identified. All of the Columbian WTD carried alleles that in other mainland populations are associated with relatively high susceptibility to CWD. While larger sampling is needed, future management plans should consider that Columbian WTD are likely to be genetically more vulnerable to CWD than many other WTD populations. Finally, we suggest that genetic vulnerability to CWD be assessed by sequencing PRNP across other endangered cervids, both wild and in captive breeding facilities.